2016
DOI: 10.1108/ijem-09-2015-0125
|View full text |Cite
|
Sign up to set email alerts
|

Size matters

Abstract: Purpose – The purpose of this paper is to examine the relationship between staff size and perceived organizational support (POS) in early childhood education (ECE) organizations. Design/methodology/approach – A territory-wide questionnaire survey was designed to investigate the perceptions of preschool teachers in Hong Kong on four dimensions of organizational support, namely, teacher participation in decision making, school management s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Similar changes have been noticed elsewhere, and the growing number of staff has been seen to increase challenges (Ho et al, 2016). Consequently, ECE teachers' ability to participate in decisionmaking and receive support from the ECE leader seem to have decreased (Ho et al, 2016). According to Keski-Rauska et al's (2016) research concerning distributed leadership model in Finnish ECE, the teachers felt that the number of staff for the two leaders in a decentralized unit reduced the time available to interact with ECE teachers.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar changes have been noticed elsewhere, and the growing number of staff has been seen to increase challenges (Ho et al, 2016). Consequently, ECE teachers' ability to participate in decisionmaking and receive support from the ECE leader seem to have decreased (Ho et al, 2016). According to Keski-Rauska et al's (2016) research concerning distributed leadership model in Finnish ECE, the teachers felt that the number of staff for the two leaders in a decentralized unit reduced the time available to interact with ECE teachers.…”
Section: Introductionsupporting
confidence: 62%
“…ECE leaders are leading units formed of two or more centers, and the number of employees has increased (Eskelinen and Hjelt, 2017). Similar changes have been noticed elsewhere, and the growing number of staff has been seen to increase challenges (Ho et al, 2016). Consequently, ECE teachers' ability to participate in decisionmaking and receive support from the ECE leader seem to have decreased (Ho et al, 2016).…”
Section: Introductionmentioning
confidence: 54%
“…Also, an intervention study in which the intervention group was provided with grants and funding for quality improvement and professional development as well as on-site coaching, showed improvement in process quality compared to the control group (Boller et al, 2015 [53] ). Other US studies also reported that star ratings or quality levels of the existing state-level QRIS were related to process quality as observed with commonly used measures, such as the ECERS, CLASS Pre-K or CIS, although it mainly distinguished the lowest from the highest quality centres and did not reveal differences across all star or quality levels (Hestenes et al, 2015 [54] ; Lahti et al, 2015 [55] ; Lipscomb et al, 2017 [56] ). A more detailed investigation of staff characteristics measured by the QRIS showed that particularly director's qualifications were related to higher process quality, more than classroom staff qualifications (Lipscomb et al, 2017 [56] ).…”
Section: Accountability or Quality Rating And Improvement Systemsmentioning
confidence: 76%
“…While the number of children per adult and per classroom are known indicators of ECEC quality (Cryer et al, 1999 ), few studies have examined the relationship between the overall number of children and quality. Ho et al ( 2016 ) found that teachers working in smaller services reported higher perceived organisational support, including participation in decision making and support from management, and lower organisational negativity than their counterparts in medium and large settings. In contrast, Wong et al ( 2012 ) noted that centres with fewer enrolled children were negatively impacted by inadequate government financial support.…”
Section: Systemic Influences On Quality In Ececmentioning
confidence: 99%